Risk factors for postoperative hypokalemia in patients undergoing endoscopic pituitary adenoma resection: a retrospective cohort study - Maoxiang Li; Changhong Mo; Sifan Yan; Ruijing Zhao; Weijian Luo; Lu Yang; Hao Wang; Jiliang Hu (PeerJ, 2024)
Background Currently, endoscopic transsphenoidal surgery is the primary approach for treating pituitary tumors. While endoscopic surgery offers numerous advantages, it also comes with a series of potential surgical complications. Postoperative hypokalemia is a common complication, with mild cases presenting with atypical symptoms such as dizziness, headache, fatigue, and constipation, while severe cases can lead to arrhythmias, rhabdomyolysis, and even death. Therefore, early identification of risk factors for postoperative hypokalemia is crucial. This study aims to analyze the risk factors for hypokalemia after endoscopic pituitary tumor resection. Methods and Materials This study included 168 patients who underwent endoscopic resection of pituitary tumors between 2019 and 2023. Patients were divided into hypokalemia group and non-hypokalemia group based on whether their postoperative serum potassium concentration was less than 3.0 mEq/L. Identifying independent risk factors through binary logistic regression analysis. Results Among the 168 patients, 18 (10.7%) cases experienced postoperative hypokalemia, with the majority occurring on the fourth day after surgery. The majority of patients did not exhibit clinical symptoms related to hypokalemia. The binary logistic regression analysis revealed that age (OR 1.09; 95% CI [1.03–1.15]; P = 0.001) and postoperative hypoalbuminemia on the first day (OR, 4.35; 95% CI [1.38–13.75]; P = 0.012) were associated with postoperative hypokalemia. Conclusions Patients aged ≥50 years and those presenting with hypoalbuminemia on the first postoperative day were more likely to develop postoperative hypokalemia. Therefore, electrolyte monitoring should be enhanced in such patients postoperatively, especially to actively prevent hypokalemia on the 4th–5th postoperative day.